2021
DOI: 10.3390/app11167419
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Bioactive Compounds of Lamium album Flower Extracts Obtained by Supercritical Fluid Extraction

Abstract: In this research, supercritical CO2 extraction is applied to extract bioactive compounds from Lamium album (white dead nettle, Lamiaceae). Extraction was performed at various temperatures (40, 50, and 60 °C) using methanol as co-solvent at a constant flow rate of CO2, methanol, and pressure. The collected extracts were characterized in terms of antioxidant capacity by using DPPH, ABTS and FRAP in vitro antioxidant activity assays, whereas the Folin–Ciocalteu procedure was employed to estimate the total phenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…On this basis, finding various extraction strategies to overcome this difficulty becomes a critical step to improve extraction efficiency and/or selectivity. Or, using dedicated aids/energy-intensive intrants, such as microwave-assisted extraction [50], pressurized liquid extraction [51], supercritical fluid extraction [52], ultrasound-assisted extraction, cold plasma-assisted extraction [53], high pressure assisted extraction [54], pulsed electric field assisted extraction [55], and enzyme-assisted extraction [56], is well documented in the scientific literature as an efficient alternative. In general, while studying plant-derived chemicals, the method and solvents utilized for extraction must be carefully adopted [57].…”
Section: Non-conventional Extraction Techniquesmentioning
confidence: 99%
“…On this basis, finding various extraction strategies to overcome this difficulty becomes a critical step to improve extraction efficiency and/or selectivity. Or, using dedicated aids/energy-intensive intrants, such as microwave-assisted extraction [50], pressurized liquid extraction [51], supercritical fluid extraction [52], ultrasound-assisted extraction, cold plasma-assisted extraction [53], high pressure assisted extraction [54], pulsed electric field assisted extraction [55], and enzyme-assisted extraction [56], is well documented in the scientific literature as an efficient alternative. In general, while studying plant-derived chemicals, the method and solvents utilized for extraction must be carefully adopted [57].…”
Section: Non-conventional Extraction Techniquesmentioning
confidence: 99%
“…Additionally, the study reported that the SCE improved the yield of bioactive compounds when compared with other extraction techniques (Pimentel-Moral et al, 2019). Similarly, methanol was used as a co-solvent for SCE extraction of bioactive compounds from Lamium album flower (Uwineza et al, 2021). The results indicated that the obtained extract had high antioxidant properties (estimated using FRAP, ABTS, and DPPH assays) and the presence of co-solvent had significantly influenced the phenolic content in the extract (Uwineza et al, 2021).…”
Section: Supercritical Co 2 Extractionmentioning
confidence: 96%
“…Similarly, methanol was used as a co-solvent for SCE extraction of bioactive compounds from Lamium album flower (Uwineza et al, 2021). The results indicated that the obtained extract had high antioxidant properties (estimated using FRAP, ABTS, and DPPH assays) and the presence of co-solvent had significantly influenced the phenolic content in the extract (Uwineza et al, 2021). Besides this, SCE also reported for the extraction of other biomolecules such as lipids (especially polyunsaturated fatty acids and omega-6 fatty acids), proteins, from the cells of microalgae (Sarkar et al, 2022).…”
Section: Supercritical Co 2 Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food industries nowadays are interested in finding natural food additives, such as colorants and preservatives, that are stable to develop and have functional derivative products [6][7][8]. C. ternatea can be a great source of natural food additives due to its bioactive compounds, especially anthocyanin.…”
Section: Introductionmentioning
confidence: 99%